Analisis Politik Alih Kewenangan Pengelolaan Guru Sma/Smk Dari Pemerintah Kabupaten/Kota Kepada Pemerintah Provinsi - Nunik Retno Herawati (Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Under Law 23 of 2014 on Regional Government, there is a change in the distribution of functions in the management of education. High education previously managed by district / municipality governments turned to the provincial government. This article aims to analyze teachers management before and After the transition of the high education authority of the Regency / City government to the Provincial Government of Central Java using political perspective. Decentralization system has basically opened wide opportunity for each region to play a bigger role, including in the management of teachers in the District / City. Domination of the Head of Region is very visible in the process of recruitment, selection, payroll, career development, placement, mutation and Evaluation Performance Teacher District / City. The recentralization of high education authority, especially the management of teachers at the Provincial Government level, is expected to minimize the occurrence of education politicization at the district / municipality level.